A critical review of detection and classification of power quality events. (January 2015) - Mahela, Om Prakash; Shaik, Abdul Gafoor; Gupta, Neeraj
Abstract: Requirement of green supply with higher quality has been consumers' demand around the globe. The electrical power system is expected to deliver undistorted sinusoidal rated voltage and current continuously at rated frequency to the consumers. This paper presents a comprehensive review of signal processing and intelligent techniques for automatic classification of the power quality (PQ) events and an effect of noise on detection and classification of disturbances. It is intended to provide a wide spectrum on the status of detection and classification of PQ disturbances as well as an effect of noise on detection and classification of PQ events to the researchers, designers and engineers working on power quality. More than 150 research publications on detection and classification techniques of PQ disturbances have been critically examined, classified and listed for quick reference.